Work behavior and productivity of LTO-Region VI rank and file employees - Balete, Vences; Herrera, Sarah Jane.; Tala-oc, Honeylet; Valenzuela, Cristian Joy. (2005.)
This study focuses on employees' work behaviour and level of productivity of LTO-Region VI rank and file employees. The primary tool of the study is the questionnaire which is filled up by the employees. Secondary was sourced from the internet and library. The respondents include fifteen (15) LTO rank and file employees. This study revealed that the work behaviour of LTO rank and file employees strongly affects the level of productivity of the organization. Some factors that affect productivity are salaries and other economic incentives received by employees as well as recognition from top management. The group also suggested several solution to the management in order to increase the level of productivity of their subordinates.
Research Study (Mgt 199-Management Research). -- [Iloilo City] : University of the Philippines Visayas-College of Management, October 2005.